A study of scalability over MPLS VPN / Abd Karim Md Sah - Md Sah, Abd Karim (Faculty of Information Technology and Quantitative Sciences, 2005)
Nowadays, new technology of IP forwarding has been widely produced. Multi Label Switching Protocol (MPLS) is the new technology that combination of traditional network layer 3 routing protocol and layer 2 switching technologies. This technology has proven its value for delivering new services while at the same time allowing migration from old to new networks. In this project we are going to do testing and implement scalability over MPLS. This testing and implementation are to proof the scalability is the one important thing when design MPLS technology. We also do research and study about MPLS network, how this network can be a simple network to manage. What are the advantages of this technology compare the traditional network. Furthermore, we can know how this technology can solve the old technology that is based on traditional IP forwarding only. When this technologies are more important and suitable for WAN network. Scalability is the one of the criteria that should be analysis before design the network. This report will describe how to configure MPLS in one network, analyze and test the network to proof the important of the scalability over MPLS. From this analysis and testing we can know the dynamics of growth in the networks as new customers are added, as well as the ultimate limits of their networks.